Molecular Characterization of Staphylococcus aureus Isolates Obtained from Hemodialyzed Patients at the Hospital de Clínicas of Paraguay: A pilot study - Rubén Arturo Silvero Isidre; Fátima Rodríguez Acosta; César Rodrigo Cristaldo Vargas; Genaro Américo Velázquez Romero; José Félix Plans Perrota; Rosa María Guillén Fretes (University Library System, University of Pittsburgh, 2017)
Background: Patients undergoing hemodialysis are susceptible to the nasal carriage of Staphylococcus aureus, increasing the risk of developing infections associated with higher morbidity and mortality. The objective of this study was to describe the frequency of S. aureus carriage in hemodialysis patients and to perform molecular analysis of isolates by applying multiple-locus variable analysis. Methods: We conducted a descriptive cross sectional study with non-probabilistic sampling that included 28 hemodialysis patients attending the Nephrology Department of Hospital de Clínicas in Asunción, Paraguay. We obtained clinical data from medical records and interviews with patients. Nasal swabs were collected and analyzed by microbiological and molecular methods. Results: The frequency of S. aureus carriage was 50% (14/28), 93% of which (13/14) were methicillin resistant, 57% (6/14) were gentamicin resistant and 36% (5/14) were resistant to more than 4 antibiotic classes. S. aureus carriers showed higher frequency of rhinitis (p=0.02 odds ratio [OR]=6.6 (1.2- 34.4)). Seven methicillin-resistant S. aureus isolates had been analyzed by multiple-locus variable analysis, two of them showed identical pattern bands. Conclusion: We found a high frequency of methicillin-resistant Staphylococcus aureus colonization and the presence of two isolates with identical profile in the multiple-locus variable analysis indicating the possibility of transmission between patients.